Cytotoxic and Antitumoral Activity of N-(9H-purin-6-yl) Benzamide Derivatives and Related Water-soluble Prodrugs - Cros-Perrial, Emeline; Saulnier, Steve; Raza, Muhammad Z.; Charmelot, Rémi; Egron, David; Dumontet, Charles; Chaloin, Laurent; Peyrottes, Suzanne; Jordheim, Lars Petter (Current Molecular Pharmacology, 2022)
Background: The development of small molecules as cancer treatments is still of both interest and importance. Objective: Having synthesized and identified the initial cytotoxic activity of a series of chemically related N-(9H-purin-6-yl) benzamide derivatives, we continued their evaluation on cancer cell models. We also synthesized water-soluble prodrugs of the main compound and performed in vivo experiments. Method: We used organic chemistry to obtain compounds of interest and prodrugs. The biological evaluation included MTT assays, synergy experiments, proliferation assays by CFSE, cell cycle distribution and in vivo antitumoral activity. Results: Our results show activities on cancer cell lines ranging from 3-39 μM for the best compounds, with both induction of apoptosis and decrease in cell proliferation. Two compounds evaluated in vivo showed weak antitumoral activity. In addition, the lead compound and its prodrug had a synergistic activity with the nucleoside analogue fludarabine in vitro and in vivo. Conclusion: Our work allowed us to gain better knowledge on the activity of N-(9H-purin-6-yl) benzamide derivatives and showed new examples of water-soluble prodrugs. More research is warranted to decipher the molecular mechanisms of the molecules.
Keywords: pharmacology